Increasing prevalence of papillary thyroid carcinoma in recent years in greece: The majority are incidental - Alevizaki, M.; Papageorgiou, G.; Rentziou, G.; Saltiki, K.; Marafelia, P.; Loukari, E.; Koutras, D.A.; Dimopoulos, M.-A. (Thyroid, 2009)
Background: New cases of well-differentiated thyroid cancer (DTC) are diagnosed more frequently worldwide. We investigated trends and differences in clinical and histological characteristics of new DTC cases presenting in one large center. Methods: During the last 34 years 852 follicular cell-derived DTC cases (83% papillary [PTC], 17% follicular [FTC] carcinoma) presented in the Endocrine Unit of the Department of Clinical Therapeutics in Alexandra Hospital (18.8% men, mean age 42.4±14.5 years). Patients were classified in three period groups according to year of diagnosis: period 1, 1963-1982; period 2, 1983-1992; and period 3, 1993-2007. We recorded the histological type, age at diagnosis, and, in period 3, the type of pre-existing thyroid disease, the stage, and tumor size. Results: During periods 1, 2, and 3, the mean age at diagnosis was 37.7±12.3, 42.4±14.53, and 44.1±14.9 years (p=0.001), respectively, and the male to female ratio was similar. The prevalence of FTC was 22.7%, 28.1%, and 6.5%, respectively. In period 3, 51.6% of the PTCs were microcarcinomas (microPTC) ≤10mm; these patients tended to be older (p=0.09). Microcarcinomas were more frequent among patients operated for pre-existing multinodular goiter (MNG) or prominent hot nodule compared to pre-existing single cold nodule (p<0.001, Pearson χ2). In period 3, 88% of the microPTC diagnoses were incidental. Of the incidental microPTCs detected in MNG, 25% had capsular invasion, 4.5% had lymph node involvement, and 3.6% had soft tissue involvement. Conclusions: We hypothesize that the prevalence of FTC during the last decade in our center in Greece was very low due to correction of iodine deficiency and a relative increase in the prevalence of microPTC. More than 50% of PTC diagnosed during the last decade were microPTCs that were detected incidentally in older persons with preexisting MNG or a prominent hot nodule. This is one of the highest, if not the highest percentage of microPTCs that were incidentally detected. Despite many of these having features of invasiveness, most appear to remain clinically silent. Research is needed to identify factors predisposing microPTCs to evolve from a subclinical to a clinically apparent form. © 2009 Mary Ann Liebert, Inc.